Leveraging health financing, digital health and self-care approaches to strengthen maternal health journeys in India: perspectives from Assam - Ramesh, Sowmya; Warren, Charlotte E.; Bellows, Ben; Dwivedi, Himanshi; Gupta, Himani; Munjral, Ashita; Rawat, Swapnil; Tresner-Kirsch, David; Nagpal, Jitender (Frontiers in Global Women's Health, 2025)
Maternal morbidity and mortality in India continue to be high in populations and places with limited access to quality health services. Major barriers include out of pocket expenditure, lack of autonomy and information around maternal health services and weak implementation of pro-poor policies. Addressing demand-side barriers and enablers is critical to improving healthcare uptake and healthcare adherence along the pregnancy-postnatal continuum. This paper describes three well known operational spaces, maternal health financing, digital health, and self-care interventions within the Indian context including pro-poor maternal health policies, mobile health ecosystems and networks, and self-care opportunities that promote women's knowledge, choice, self-efficacy, and autonomy. These are expanded on to identify additional opportunities to improve access to MH services. Finally, the authors describe a new digital health intervention using a chat-based digital support system that has the potential to reduce barriers that women face in seeking and receiving quality MH services in Assam and elsewhere. Future work on how to implement such a combined approach need to account for multiple contextual factors, including understanding the nature and success of national pro-poor MH policies in each state, how the public and private health systems function and interact, social determinants of health as well as engaging women in the process to improve maternal and newborn health outcomes.